2007
DOI: 10.1097/01.pgp.0000228145.36807.43
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade Fibromyxoid Sarcoma Presenting Clinically as a Primary Ovarian Neoplasm

Abstract: Low-grade fibromyxoid sarcoma is an uncommon, deceptively bland mesenchymal neoplasm that typically occurs in the deep soft tissues of the proximal extremities of young to middle-aged patients. Intra-abdominal low-grade fibromyxoid sarcomas are distinctly rare. We describe the first reported example of this sarcoma involving the ovary. The 42-year-old patient presented with progressing abdominal pain and urinary frequency. Computed tomographic imaging of the abdomen and pelvis showed a 14-cm left-sided pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…[2][3][4][5] Increasingly, LGFMS is being reported at unusual sites, including inside solid organs. 5,[9][10][11][12] The tumor is well known for its propensity for local recurrence, with metastasis also seen in a subset of cases. 3,5 Surgical excision remains the treatment of choice, although some patients received additional chemotherapy and radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Increasingly, LGFMS is being reported at unusual sites, including inside solid organs. 5,[9][10][11][12] The tumor is well known for its propensity for local recurrence, with metastasis also seen in a subset of cases. 3,5 Surgical excision remains the treatment of choice, although some patients received additional chemotherapy and radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly reported to arise from the deep soft tissues of the lower extremities, particularly the thigh, but occasionally reported to arise also, from the chest wall, axilla, inguinal region, buttock, neck, the mediastinum and brain 2 . Abdominal LGFMS is extremely rare, it had been reported to arise from small bowel mesentery, colon, falciform ligament, retroperitoneum, and the ovary 3,4,5 .They are commonly seen in the young or middle-aged adult, although it can occur even at the extremes of life.The literature on LGFMS is still sparse, although it is growing. All the report on this disease comes from western country and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…There is some suggestion that the published series with lower recurrence rates had higher rates of initial gross-total resection. 2,3,5,6,18 Surgery is the treatment of choice for local recurrence and for metastatic lesions. Other authors have reported treatment with chemotherapy or radiation therapy, but there is no convincing evidence that this alters the outcomes.…”
Section: Pathologymentioning
confidence: 99%
“…Chondrosarcoma tends to be positive for vimentin and S-100; this tumor was negative. [11][12][13][16][17][18] The tumor was negative for cytokeratin and smooth muscle actin which, along with vimentin and S-100, are suggestive of liposarcoma. Myxofibrosarcoma show much more cellular atypia than those in this tumor.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation